Surgical management of unilateral rhegmatogenous retinal detachment associated with ocular coloboma in a 7-year-old child with Noonan syndrome - Bastion, Mae-Lynn Catherine (BMJ Publishing Group, 2011)
The authors would like to present an unusual case of unilateral retinal detachment, phacodonesis, dense cataract and ocular coloboma in a 7-year-old Indian Muslim boy with Noonan syndrome. He underwent lensectomy, 23G pars planar vitrectomy, air fluid exchange, endolaser and silicone oil injection which successfully reattached the retina. His best corrected visual acuity was 6/24 6 months after the surgery and oil removal.